ANXIETY AND DEPRESSION RATES AMONG THE UNEMPLOYED CITIZENS OF LATGALE REGION - Fokina, Olga; Vasiļjeva, Ērika; Millere, Inga; Deklava, Liāna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Employment status can substantially influence emotional, social and financial welfare of an individual, protects an individual from obvious negative influence on a person’s life quality. This is connected with a loss of work, instability and low income, as well as worsening of life quality. According to the gained data, unemployed people feel depression and anxiety symptoms very often and it is not paid enough attention to these symptoms. Taking into consideration the fact, that in Latgale region the level of unemployment is the highest one, it would be important to define the signs of depression and anxiety among the unemployed people. The second purpose of the research is to find out the connection between anxiety and depression indexes among the unemployed people and the duration of an unemployed person’s status. 100 participants were involved in the research. To gain the data the quantative method of reseach was used. The two types of instruments were used: Spielberg’s self-assessment anxiety test and Beck depression scale. The connection between the duration of unemployed status and depression and anxiety symptoms was not verified.